GE_GERICHTE C/7502/2012 vom 6. März 2015 - GE Cour de justice (2015)
VENTE; ENTREPRENEUR; GARANTIE EN RAISON DES DÉFAUTS DE LA CHOSE; INTERPRÉTATION(SENS GÉNÉRAL) | CPC.237; CPC.308.1; CO.18; CO.164; CO.197; CO.221; CO.368